Previdência privada fechada: (in)adequação ao objetivo de garantia do benefício contratado - Barbara Menezes Monduzzi (2016)
The present work aims to study the legal regime of closed private pension funds and verify if it was built accordingly to the objective of securing the pension to the beneficiaries, pursuant to article 202 of the Constitution of the Federative Republic of Brazil, signalizing what could represent a risk to that objective and, therefore, to the principle of protection of trust. The research has a multidisciplinary approach, with investigations in the field of Law, following the legal-dogmatic aspects of the issue. Takes as theoretical framework the studies developed for Claus-Wilhelm Canaris about the systems theory applicable to the Law and the principle of protection of trust. The conclusions are intended to be comprehensive, applicable to all relevant parts of the system. The present research was developed as a condition to obtain the title of Master of Law for the Federal University of Minas Gerais (Brazil).